Critical Inter-Load Spacing for Hogging Moments in Three-Span Bridges. (November 2018) - Caprani, C.C.
Abstract: This article outlines the determination of the inter-load spacing between two equal point loads traversing a continuous three-span beam, such that the bending moment at the first interior support is a maximum. Different side-span ratios are considered. Exact closed-form expressions are derived, as well as a simple close approximation, making the results easy to implement in spreadsheets and other software. It is motivated by the use of load models from older codes of practice. Bridge owners often make access decisions for heavy vehicles based on the as-built capacities of bridges and a useful proxy for the capacity is the code load model used for the bridge's design. Some of these older load models require two equal point loads for determining the design hogging moments, such as the 1970 NAASRA code in Australia. As such, where applicable, this work will help facilitate the efficient filtering of problematic bridges for more refined structural analyses when making heavy vehicle permit access decisions.